Analisis Efektivitas Upaya Rehabilitasi terhadap Anak sebagai Pecandu Narkoba : Pendekatan Medis dan Psikosisial - Almanda Putri Andini; Uut Rahayuningsih; Ayyesha Salsabila; Faris Hasan Aziz (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This study discusses the effectiveness of medical and psychosocial interventions in the rehabilitation of drug addicted children. Drug abuse in children is a serious problem that can damage a person's physical and mental health and threaten the future of the nation. The main solution in a situation like this is rehabilitation, which aims to eliminate the child's physical dependence and also restore the child's social and psychological condition so that they can interact with others normally again. This study examines how rehabilitation programs are implemented in Indonesia. This study examines problems such as limited facilities, social stigma, lack of personnel, and the ineffective combination of medical and psychosocial approaches. In addition, this study examines Law Number 35 of 2009 concerning Narcotics which regulates the rehabilitation of drug addicted children. This study shows that successful rehabilitation must combine medical treatment and psychological and social support from families, health workers, psychologists, and the surrounding environment and society also need to help. This method not only helps children recover from addiction, but also prevents them from being treated as criminals and helps them be accepted back into the social environment. Therefore, in order for this program to be more friendly, continue to run well, and provide long-term benefits for children and society, cooperation from various parties and improvement of the quality of rehabilitation services are needed.